2010
DOI: 10.2139/ssrn.1535995
|View full text |Cite
|
Sign up to set email alerts
|

Do Bank Loans and Credit Standards Have an Effect on Output? A Panel Approach for the Euro Area

Abstract: The views expressed in this paper do not necessarily refl ect those of the European Central Bank. Information on all of the working papers published in the ECB's Working PaperSeries can be found on the ECB's website, http://www.ecb.europa.eu/pub/scientifi c/ wps/date/html/index.en.html

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…In recent years, the literature has graduated to focusing on the impact of credit flows (as opposed to stocks) on GDP. Cappiello et al (2010) find a non-negligible positive relationship between growth in credit flows and GDP growth for the Euro area, in contrast to Driscoll (2004) finding less such evidence for the United States. Since Borensztein et al (1998), many studies have also found a positive relationship between FDI and growth, as summarized in Ozturk (2007), again to varying degrees.…”
Section: Empirical Analysis: Does It Matter Which Sectors Foreign Cap...mentioning
confidence: 63%
“…In recent years, the literature has graduated to focusing on the impact of credit flows (as opposed to stocks) on GDP. Cappiello et al (2010) find a non-negligible positive relationship between growth in credit flows and GDP growth for the Euro area, in contrast to Driscoll (2004) finding less such evidence for the United States. Since Borensztein et al (1998), many studies have also found a positive relationship between FDI and growth, as summarized in Ozturk (2007), again to varying degrees.…”
Section: Empirical Analysis: Does It Matter Which Sectors Foreign Cap...mentioning
confidence: 63%
“…Demirguc-Kunt and Huizinga (2000) and Bikker and Hu 12 For example, in the U.S. (where the total bank loans to the private sector to GDP ratio stood at 63% in 2007) during the period 1965-2004 the amount and cost of bank financing did not have a substantial impact on economic activity (Driscoll, 2004). In contrast, for the euro area (where the relevant figure is much higher), Cappiello et al (2010) found that during the period 1999-2008 loan supply had a positive impact on economic activity. 13 See Bikker and Metzemakers (2005) and Lucas and .…”
Section: Profitability and Procyclicalitymentioning
confidence: 97%
“…2009c and Cappiello et al, 2010). Τhis channel also includes the bank capital channel 28 ; and the balance sheet channel (also called broad credit channel 29 ), through which potential borrowers' property and collateral value is affected.…”
Section: Economic Policy and Banking Supervisionmentioning
confidence: 99%
“…Global economic confidence plunged, driving down production, investment and consumption. This was accompanied by a credit squeeze, with credit to households and firms drying up (European Central Bank, 2009;Hempell and Kok, 2010;Cappiello et al, 2010;and Maddaloni and Peydró, 2011). Within a few months, the euro area had entered its own severe recession, which lasted from the second quarter of 2008 until the third quarter of 2009.…”
Section: Financial Turmoil: August 2007 To September 2008mentioning
confidence: 99%